Case report: Clinical and single-cell transcriptome sequencing analysis of a mixed gangliocytoma-adenoma presenting as acromegaly - Li, Chao; Feng, Daqin; Zhou, Dabiao (Frontiers in Oncology, 2022)
Background：Mixed gangliocytoma-adenoma (MGA) is a rare tumor of pituitary gland. It’s difficult to distinguish it from pituitary adenoma by clinical manifestations, imaging features or serological testing. Thus, the histopathological examination is still the golden standard for diagnoses of this disease. Besides, studies on molecular level are still lacking. Case information：In this case report, we describe a 28-year-old male with MGA presenting as acromegaly, who suffered staging operation and post-operation gamma knife radiosurgery, but finally died of secondary hyperglycemic hyperosmolar collapse. A complete data including clinical, histopathological, ultrastructural and single-cell transcriptome level information are collected and analyzed. Conclusion: This case report details the only clinical and molecular report of MGA following operation and radiotherapy. Complete clinical data enhance the understanding of the diagnosis and treatment of this disease. Besides, the single-cell transcriptome sequencing analysis further disclose the intra-tumoral heterogeneity and will provide support for subsequent basic research.